PENDUGAAN UMUR CAKALANG, Katsuwonus pelamis (Linnaeus, 1758) YANG DIDARATKAN DI UPT P2SKP PONDOKDADAP SENDANGBIRU MELALUI ANALISIS LINGKARAN UMUR - Yesika Nanda Pramurdya; Irwan Jatmiko; Muhammad Arif Rahman; Dewa Gede Raka Wiadnya (JFMR (Journal of Fisheries and Marine Research), 2019)
Abstract Length-growth analysis of fish cannot be completed without age information. Age study on skipjack has been done through analysis of its first-hard dorsal fin. Sampling was done using 11 fish specimen taken from UPT P2SKP Pondokdadap Sendangbiru, from January to February 2018. Species identification follows the FAO standard procedure (species identification sheet) published 2001. A specimen was deposited at Depository Ichtyologicum Brawijaya with code DIB.FISH 111103. The first hard spine of 11 fish samples were cut with IsoMet low speed cutting machine at 50 mm thickness. The preparates were then analyzed using biological binocular microscope at 40x magnification. The results showed differences in number of growth annuli (annual growth-ring) at different fish length (FL). The number of annuli varied between 4 - 6+ age year at fish length (FL) variation between 38 and 62 cm. These values were closely related to those with other methods such as Modal Progression Analysis (MPA). The number of samples successfully analyzed (5 specimen) were not sufficient for analysis of length-growth parameters (L∞, k and t0). Also, this technique did not apply for age less than yearly unit, but quite affordable (Rp.50.000,- per sample) for a fairly variable amount of specimens.